A Lead Carboxylate‐Azolate Metal‐Organic Framework Based on Hexanuclear Clusters: Luminescence and Accelerating the Thermal Decomposition of Ammonium Perchlorate. Issue 3 (12th March 2019) - Liu, Ge; Wu, Shuo; Hou, Lei; Lu, Yu‐Ke; Yang, Qi; Wang, Yao‐Yu
Abstract: A lead carboxylate–azolate framework, [Pb3 (μ4 ‐O)(L)2 (H2 O)] ⋅ 2H2 O (1 ), has been constructed from the reaction of 2‐methyl‐4‐(1H‐tetrazol‐5‐yl) benzoic acid (H2 L) and Pb(NO3 )2 under solvothermal conditions. Compound1 contains an unprecedented hexanuclear cluster [Pb6 (μ4 ‐O)2 (COO)4 (CN4 )2 ], which as an 8‐connected node is connected by 3‐connected L linkers to give rise to a three‐dimensional framework with an uncommon (3, 8)‐connected tfz‐d; UO3 topology. Framework1 possesses strong solid‐state yellow luminescence (563 nm), which stems from ligand‐to‐metal charge transfer (LMCT), however, the removal of water molecules in1 lead to the significant luminescent decrease of the sample. Importantly, in the presence of1, the thermal decomposition of ammonium perchlorate is significantly accelerated. Abstract : MOFs make things faster : A metal‐organic framework (MOF) based on hexanuclear [Pb6 (μ4 ‐O)2 (COO)4 (CN4)2 ] clusters was prepared by using a 2‐methyl‐4‐(1H‐tetrazol‐5‐yl) benzoic acid ligand. The MOF has a (3, 8)‐connected tfz‐d; UO3 topology, and undergoes luminescence changes caused by the removal of water. It also accelerates the thermal decomposition of ammonium perchlorate.